Separação de gases por membranas de fibra oca revestida com nanopartículas de óxido de grafeno - Ribeiro, Stella Rodrigues Ferreira Lima (2022)
Graphene oxide (GO) membranes are suitable for hydrogen (separation) mainly due to H_2 〖CO〗_2the transport microenvironment that the GO membrane provides. The way in which the layers are stacked can influence gas permeation, and therefore the deposition of a selective and highly permeable GO membrane on a suitable substrate is still a challenge. In this work we applied the vacuum assisted method to deposit GO layers in hollow alumina and spinel fibers with asymmetric pore distribution. Initially, 4 GO synthesis routes based on the modified Hummers method were evaluated. The methods differ from each other by the proportion of reagents, temperature control and exfoliation method. The suspensions named as OG1 and OG2 were produced with the same proportion of reagents, but the OG2 sample was maintained for longer (20 h) than the OG1 sample (1 h) at oxidation temperature close to 90°C. On the other hand, the exfoliation of the OG1 sample was performed in an ultrasonic bath, while the exfoliation method of the other samples produced was only mechanical agitation. For the OG3 sample, expanded graphite was used as a precursor agent and the temperature was controlled below 10°C during oxidation. The OG4 sample was synthesized using H3PO4 as an oxidizing agent, in addition to H2SO4, NaNO3 and KMnO4. The GO suspensions produced were characterized by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Fourier Transform Infrared Spectroscopy (FT-IR), Raman Spectroscopy (RAMAN), Elemental Analysis (C, H, N and O), X-ray diffractometry (XRD) and Atomic Force Spectroscopy (AFM). According to the SEM, TEM and AFM analyses, the OG1 and OG2 samples showed more organized and oxidized leaves than the OG3 and OG4 samples, probably due to the higher temperature control in the oxidation step, since the OG3 sample was not synthesized at the indicated temperature of approximately 90°C and, during the synthesis of the OG4 sample, temperature was sharply elevated by the presence of additional oxidizing agents. Elemental analysis confirmed the highest O/C ratio in the OG1 and OG2 samples. Consequently, samples OG1 and OG2 showed higher mass loss than OG3 and OG4 samples during inert atmosphere heating up to 900°C (TGA analysis). XRD analyses also showed a higher oxidation of graphite in the OG1 and OG2 samples, which was visualized by the decrease of the graphitic domain for the oxidized graphite domains. The RAMAM spectra of the GO samples showed the expected characteristic peaks. The oxidized functional groups were more evident in the FT-IR spectra of the OG1 and OG2 samples than of the OG3 and OG4 samples. Therefore, for the present work, the synthesis and samples chosen for application of gas separation processes by graphene oxide composite membrane were OG1 and OG2. Then, hollow fibers of α-alumina and spinel were produced to act as supports of the GO membranes. The GO membranes were deposited on the supports by the vacuum-assisted dip-coating method under different conditions of concentration of the GO suspension, vacuum pressure and immersion time under vacuum. An intermediate layer of -alumina was deposited on the ceramic support in order to decrease the roughness of its outer surface. The composite GO membrane deposited on the α-alumina fiber with an intermediate layer of -alumina from a suspension at 0.1 g/L under vacuum of 600 mmHg for 2 min presented the highest H2 permeance of 70.64±0.0x10-7 mol s-1 m-2 Pa-1 and selectivity H2/N2 of 3.5 and H2/CO2 of 3.9. Compared to the literature results, however, the need for improvements in membrane selectivity for H2 is necessary, which can be later achieved by better controlling in the deposition process and consequent reduction of defects in the GO layer. In fact, although the -alumina layer provides a decrease in membrane roughness, the adhesion of the GO membrane on the support is impaired in this situation. In order to produce a composite GO membrane for CO2 separation, GO layers were deposited on the ceramic support from different concentrations of the GO suspension under vacuum at 200 mmHg for 10 min. In this case, the crosslinking of GO with with etilenodiamine favored CO2 permeation by the membrane, resulting in CO2 permeance of approximately 40x10-7 mol s-1 m-2 Pa-1 and CO2/N2 selectivity greater than 40. This result is superior or equivalent to the results reported in the literature for GO membranes. Therefore, this work allowed a deepening of knowledge about the synthesis of GO and favorable results for gas permeation in the composite membranes of GO produced.